Characterization and Production of Rhamnolipid Biosurfactant in Recombinant Escherichia coli Using Autoinduction Medium and Palm Oil Mill Effluent - Sony Suhandono; Subhan Hadi Kusuma; Karlia Meitha (Brazilian Archives of Biology and Technology, 2021)
Abstract Rhamnolipid is a potent biodegradable surfactant, which frequently used in pharmaceutical and environmental industries, such as enhanced oil recovery and bioremediation. This study aims to engineer Escherichia coli for the heterologous host production of rhamnolipid, to characterize the rhamnolipid product, and to optimize the production using autoinduction medium and POME (palm oil mill effluent). The construction of genes involved in rhamnolipid biosynthesis was designed in two plasmids, pPM RHLAB (mono-rhamnolipid production plasmid) and pPM RHLABC (di-rhamnolipid production plasmid). The characterization of rhamnolipid congeners and activity using high-resolution mass spectrometry (HRMS) and critical micelle concentration (CMC). In order to estimate rhamnolipid yield, an oil spreading test was performed. HRMS and CMC result show E. coli pPM RHLAB mainly produced mono-rhamnolipid (Rha-C14:2) with 900 mg/L and 35.4 mN/m of CMC and surface tension value, whereas E. coli pPM RHLABC mainly produced di-rhamnolipid (Rha-Rha-C10) with 300 mg/L and 34.3 mN/m of CMC and surface tension value, respectively. The optimum condition to produce rhamnolipid was at 20 h cultivation time, 37 oC, and pH 7. In this condition, the maximum rhamnolipid yield of 1245.68 mg/L using autoinduction medium and 318.42 mg/L using 20% (v/v) of POME. In conclusion, the characteristics of the rhamnolipid by recombinant E. coli is very promising to be used in industries as the most economical way of producing rhamnolipid.